Community Empowerment Through Super Ganepo Umkm in Jorong Padang Kandi, Nagari VII Koto Talago, Guguak District, Lima Puluh District - Andini, Puti; Gani, Maulid Hariri; Oktayanty, Yetty (Kirana Publisher (KNPub), 2024)
This research discusses